Czech Literary Culture in the Post-Digital Era - Piorecký, Karel; Malínek, Vojtěch (Porównania, 2020)
This study examines the changes within Czech literary culture since 2000 in relation to the process of remediation. The starting methodological point is in examining a structure of a literary system within a model proposed by Siegfried J. Schmidt. The impact of new creative approaches which utilise interactive network media and also of available publishing platforms are observed in terms of the increase in the size of the literary active group of the population. The study further investigates publishing options via the Internet used mainly by amateur authors, complementary phenomena in print production, as well as the impact of these innovative forms on the dynamics of the book market. The ways in which texts are received are examined particularly from the point of enhancing the role of the reader within interactive media and attention is paid to the qualitative changes within the reception frameworks (transnational and non-literary contexts). And finally, the ways in which literary phenomena are handled is largely related to the reflection of the critical state of the current literary criticism and new virtual formats of critiquing literature. The study shows that the evolutionary changes which were brought about by extending the use of digital media within literary communication have been so extensive that the Schmidt model of analysis has proven insufficient.